Population pharmacokinetics of everolimus in patients with seizures associated with focal cortical dysplasia - Jinha Park; Jinha Park; Se Hee Kim; Jongsung Hahn; Hoon-Chul Kang; Sang-Guk Lee; Heung Dong Kim; Heung Dong Kim; Min Jung Chang; Min Jung Chang; Min Jung Chang (Frontiers Media S.A., 2023)
Background: Everolimus is an inhibitor of mammalian target of rapamycin complex 1. As mutations in TSC1 and TSC2, which cause partial-onset seizures associated with TSC, were found in focal cortical dysplasia type Ⅱ (FCD Ⅱ) patients, a clinical trial has been performed to explore the efficacy and safety of everolimus in FCD patients. However, no dosage regimen was determined to treat FCD II. To recommend an optimal dose regimen for FCD patients, a population pharmacokinetic model of everolimus in FCD patients was developed.Methods: The data of everolimus were collected from September 2017 to May 2020 in a tertiary-level hospital in Korea. The model was developed using NONMEM® software version 7.4.1 (Icon Development Solutions, Ellicott City, MD, United States).Results: The population pharmacokinetics of everolimus was described as the one-compartment model with first-order absorption, with the effect of BSA on clearance. The final model was built as follows: TVCL = 12.5 + 9.71 × (BSA/1.5), TVV = 293, and TVKA = 0.585. As a result of simulation, a dose higher than 7 mg/m2 is needed in patients with BSA 0.5 m2, and a dose higher than 6 mg/m2 is needed in patients with BSA 0.7 m2. A dose of 4.5 mg/m2 is enough in the population with BSA higher than 1.5 m2 to meet the target trough range of 5-15 ng/mL.Conclusion: Based on the developed pharmacokinetics model, the optimal dose of everolimus in practice was recommended by considering the available strengths of Afinitor disperz®, 2 mg, 3 mg, and 5 mg.